2017
DOI: 10.1007/s10822-017-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pharmacophore models derived from crystallography and NMR ensembles

Abstract: NMR and X-ray crystallography are the two most widely used methods for determining protein structures. Our previous study examining NMR versus X-Ray sources of protein conformations showed improved performance with NMR structures when used in our Multiple Protein Structures (MPS) method for receptor-based pharmacophores (Damm, Carlson, J Am Chem Soc 129:8225-8235, 2007). However, that work was based on a single test case, HIV-1 protease, because of the rich data available for that system. New data for more sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Regarding structure-based pharmacophore modeling, the use of experimental structures to build the models must prioritize some structural features obtained from both methods; as an example, it has been demonstrated that a higher flexibility obtained in structures elucidated by nuclear magnetic resonance (NMR) spectroscopy helps to focus the models on the most essential interactions with the receptor due to the presence of structural flexibility of the complexes evidenced by the method. On the other hand, models obtained by X-ray crystallography had more pharmacophore elements compared to those obtained by NMR spectroscopy (Ghanakota and Carlson, 2017 ).…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
“…Regarding structure-based pharmacophore modeling, the use of experimental structures to build the models must prioritize some structural features obtained from both methods; as an example, it has been demonstrated that a higher flexibility obtained in structures elucidated by nuclear magnetic resonance (NMR) spectroscopy helps to focus the models on the most essential interactions with the receptor due to the presence of structural flexibility of the complexes evidenced by the method. On the other hand, models obtained by X-ray crystallography had more pharmacophore elements compared to those obtained by NMR spectroscopy (Ghanakota and Carlson, 2017 ).…”
Section: Computational Methods Applied In Virtual Screening Approachesmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation can be used to address such artifacts and additionally, provide valuable information about the flexibility and thermodynamic properties of the system . PyRod, a free and open‐source Python software, combines the strength of MD simulations with structure‐based 3D pharmacophore searches by analyzing the protein environment of water molecules in protein binding pockets and subsequently generates pharmacophore features for virtual screening …”
Section: Figurementioning
confidence: 99%